Unleashing agriculture's potential for improved nutrition and health in Malawi: Conference report - 26-27 September 2011, Lilongwe, Malawi - International Food Policy Research Institute (International Food Policy Research Institute, 2012)
In February 2011, the 2020 Vision Initiative of the International Food Policy Research Institute (IFPRI) organized an international conference in New Delhi, India on “Leveraging Agriculture for Improving Nutrition and Health.” The conference brought together 1,000 stakeholders from 65 countries from the three sectors of agriculture, nutrition, and health. Their goal was to examine how agriculture could be energized to become a more powerful tool in tackling the persistent problems of food insecurity, malnutrition, and poor health. Malawi is the first country in the world to organize a national event to follow up on and translate the findings and recommendations from the global conference and develop country-specific policy actions. IFPRI’s Malawi office and its 2020 Vision Initiative, in collaboration with the Ministry of Agriculture, Irrigation and Water Development, and supported by USAID and Irish Aid, organized the conference, “Unleashing Agriculture’s Potential for Improved Nutrition and Health in Malawi” on September 26–27, 2011, in Lilongwe. This conference focused on how agricultural strategies can best be tailored to the Malawian context and result in improvements for nutrition and health. It is crucially important to make linkages—the best agricultural practices will not succeed in improving the nation’s nutritional status if there is not good nutritional care and access to health services.